Butorfanol till get - Gustafsson, Helena (2012)
Today there are no analgesic drugs approved to be used in goats. Drugs approved for use in other species are consequently being used without knowing the pharmacokinetics of these drugs in goats. The purpose of this study was to investigate the pharmacokinetics of the opioid butorphanol when given subcutaneously in goats. Subcutaneous administration might extend the half-life compared to intravenous or intramuscular administration. Eight clinically healthy, non-pregnant 6 months old female goats were used. Butorphanol, 0.2 mg/kg, or saline was given subcutaneously with a crossover design. Blood samples were taken 10 min before and 5, 15, 30, 60, 120, 240, 360, 480, 660 and 1320 min after the injection. Plasma concentrations of butorphanol were analysed with a liquid chromatography–electrospray ionization–tandem mass spectroscopy and the limit of quantification was 0.5 ng butorphanol/ ml plasma. The results showed a terminal half-life of 78.6 ± 21.7 min. After 10 ± 5.3 min (Tmax) post administration mean and median Cmax was 199 ± 265.6 ng/ml and 56.1 ng/ml, repectively. Cmax varied between the different goats, with a range between 30.5 and 770 ng/ml. Plasma concentrations higher than 30 ng/ml were achieved in all of the goats within 15 min. The mean plasma concentration after 60 min was 20.2 ng/ml with a range between 9.3 – 42.3 ng/ml which is in accordance with analgesic plasma levels in other speices, assuming 0.2 mg/kg of butorphanol given subcutaneously would maintain analgesia in goats for about 30-60 min. If long term analgesia is required, the short half-life of butorphanol makes it less appropriate because of the short dose interval required. The wide range in plasma concentrations between different goats makes subcutaneously administration of butorphanol to goats inappropriate especially as the half-life did not increase in comparison with after intravenous or intramuscular administration. In our study, the goats showed behavioral changes such as agitation, chewing on the interior and increased bleating frequency. Studies that further investigate analgesic efficacy and behavioral changes in goats are needed.